(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study investigates the role of artificial intelligence in personalizing academic writing instruction based on learners’ proficiency levels. It focuses on how AI tools can support English language learners in improving writing skills through adaptive scaffolding and individualized feedback. A mixed-methods approach was applied with B1 and B2 level undergraduate students over a four-week intervention. Participants engaged in AI-assisted writing tasks tailored to their proficiency levels. The findings show that AI-based instruction significantly improves writing performance, particularly in grammar accuracy for B1 learners and coherence and academic style for B2 learners. Overall, the study suggests that AI can serve as an effective supportive tool in academic writing instruction while complementing, rather than replacing, the teacher’s role.